2008
DOI: 10.1143/jjap.47.896
|View full text |Cite
|
Sign up to set email alerts
|

Metalorganic Vapor Phase Epitaxial Growth Parameter Dependence of Phase Separation in Miscibility Gap of InGaAsP

Abstract: The generation mechanism of the immiscibility of InGaAsP grown by metalorganic vapor phase epitaxy (MOVPE) is investigated. The growth condition dependence of the immiscibility is examined in detail using particular photoluminescence (PL) characteristics observed in the boundary composition between stable and unstable compositional regions. A lower growth rate or a larger V/III ratio is effective for suppressing phase separation. To explain this growth condition dependence, some factors related to surface ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…These results revealed that the degree of the CuPt-ordering in InGaAsP with a low arsenic content was significantly enhanced in the 630 1C-grown sample. The results for CuPt-ordering in the TED patterns are consistent with those in the photoluminescence measurements reported previously [14][15][16][17].…”
Section: Ted Observationssupporting
confidence: 91%
See 2 more Smart Citations
“…These results revealed that the degree of the CuPt-ordering in InGaAsP with a low arsenic content was significantly enhanced in the 630 1C-grown sample. The results for CuPt-ordering in the TED patterns are consistent with those in the photoluminescence measurements reported previously [14][15][16][17].…”
Section: Ted Observationssupporting
confidence: 91%
“…The suppression of the phase separation was quantitatively understood by the formation of the CuPt-ordering in InGaAsP [15]. The CuPt-ordering is easily formed on the reconstructed surface, but at higher temperatures the adatom diffusion along the surface disrupts the surface reconstruction and therefore suppresses the CuPt-ordering [16]. Therefore, there is a competitive relationship between the CuPt-ordering and the phase separation via the surface reconstructions.…”
Section: Cupt-ordering and Phase Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas for wavelengths below 690 nm strained ternary InGaP quantum wells (QWs) can be employed as active regions, the wavelength range between 690 and 720 nm can be better addressed with tensile-or compressive-strained QWs consisting of quaternary InGaAsP [7][8][9]. Growth of compressively strained InGaAsP layers by metalorganic vapour phase epitaxy (MOVPE) is known to be challenging due to the occurrence of phase separation [10][11][12]. This tendency is strongest for mid-range compositions and lower growth temperatures and is usually referred to as the miscibility gap [10].…”
mentioning
confidence: 99%
“…Growth of compressively strained InGaAsP layers by metalorganic vapour phase epitaxy (MOVPE) is known to be challenging due to the occurrence of phase separation [10][11][12]. This tendency is strongest for mid-range compositions and lower growth temperatures and is usually referred to as the miscibility gap [10]. Therefore, the growth conditions have to be carefully selected to obtain randomly alloyed InGaAsP QWs.…”
mentioning
confidence: 99%